Peningkatan Pengenalan Budaya Jawa Melalui Media Maket Pada Anak Taman Kanak-Kanak - Suroningsih Suroningsih (AL-BURHAN, 2023)
The problem in this research is early childhood are less familiar cultures that exist in the area of residence and the media are often used for the introduction of the culture is still less attractive. The research objective was to determine the increase in culture through the introduction of media Multicultural Java Mockup in children Kindergarten in District Wedarijaksa Regency Pati. This research has been conducted in Kindergarten in District Wedarijaksa Regency Pati. The independent variable is the media Multicultural Java Mockup, while the dependent variable was the introduction of the culture. The approach used is a quantitative approach with quasi experimental design form Nonequivalent control group design. Data collection techniques using systematic observation. Techniques used in the data analysis was t-test. The results of the t test values are not given treatment group culture through the introduction of Multicultural Java Mockup of 6.426 is smaller than the value of the group given the introduction treatment through Multicultural Java Mockup at 7.447.